2005
DOI: 10.1038/sj.cdd.4401598
|View full text |Cite|
|
Sign up to set email alerts
|

NF-κB factor c-Rel mediates neuroprotection elicited by mGlu5 receptor agonists against amyloid β-peptide toxicity

Abstract: Opposite effects of nuclear factor-jB (NF-jB) on neuron survival rely on activation of diverse NF-jB factors. While p65 is necessary for glutamate-induced cell death, c-Rel mediates prosurvival effects of interleukin-1b. However, it is unknown whether activation of c-Rel-dependent pathways reduces neuron vulnerability to amyloid-b (Ab), a peptide implicated in Alzheimer's disease pathogenesis. We show that neuroprotection elicited by activation of metabotropic glutamate receptors type 5 (mGlu5) against Ab toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 86 publications
8
86
2
Order By: Relevance
“…Nuclear fractions were isolated using commercially available reagents (Nuclear Extract Kit; Active Motif, Rixensart, Belgium). DNA binding activity of NF-B subunits p50, p65, c-Rel, p52, and RelB was monitored using a commercially available ELISA-based assay (TransFactor; BD Biosciences, Mountain View, CA) (Pizzi et al, 2005). Briefly, nuclear samples (3 g) were incubated in an ELISA plate coated with oligonucleotides containing an NF-B consensus regulatory element sequence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear fractions were isolated using commercially available reagents (Nuclear Extract Kit; Active Motif, Rixensart, Belgium). DNA binding activity of NF-B subunits p50, p65, c-Rel, p52, and RelB was monitored using a commercially available ELISA-based assay (TransFactor; BD Biosciences, Mountain View, CA) (Pizzi et al, 2005). Briefly, nuclear samples (3 g) were incubated in an ELISA plate coated with oligonucleotides containing an NF-B consensus regulatory element sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, functional diversity is suggested by the unique phenotypes of knock-out mouse lines (Li and Verma, 2002). Recent evidence has shown that RelA exerts a proapoptotic and c-Rel an antiapoptotic effect in neurons (Pizzi et al, 2002(Pizzi et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from a role in promoting neuronal survival (Pizzi et al, 2002(Pizzi et al, , 2005, c-Rel has also been implicated in long-term memory (LTM) formation. Consolidation of LTM requires N-methyl-D-aspartate receptor-dependent changes in gene expression.…”
Section: C-relmentioning
confidence: 99%
“…Moreover, the c-Rel antisense made IL-1β exposure per se as toxic as the glutamate one (Pizzi et al, 2002). Further investigations confirmed that p50 and RelA subunit activation contributes to the apoptotic program in cells exposed to the β-amyloid peptide (Akama et al, 1998;Pizzi et al, 2005b;Valerio et al, 2006). In addition, the c-Rel-containing dimers p50/c-Rel and RelA/c-Rel are involved in neuroprotective effects elicited by S100B (Kögel et al, 2004), agonists at the metabotropic glutamate type 5 (mGlu5) receptors (Pizzi et al, 2005b;Sarnico et al, 2008b) or leptin (Valerio et al, 2009).…”
Section: Nf-κb In Neuron Survivalmentioning
confidence: 87%